(untitled) (Plant Tissue Culture and Biotechnology, 2008)
Considerable progress has been made in identification and cloning of genes involved in plant defense responses. With the aid of plant molecular biology and biotechnology, a large number of antifungal proteins and peptides have been isolated and assessed through in vitro bioassays. Genes and gene products that are involved in signaling pathways have also been predicted. Strategies like enhancement of plant structural defense, neutralization of fungal toxins and exploitation of antifungal genes from non-plant sources have been used to produce transgenic plants. Exploitation of these approaches has shown significant reduction of fungal diseases in many cases. Moreover, using the knowledge gathered from characteristics of these transgenic plants, it has been possible to obtain better resistance. Co-expression of multiple genes rather than single, use of inducible promoters instead of constitutive ones have been shown to give superior performance of transgenic plants. Further improvement in above strategies are however still necessary because all the above approaches have only resulted in varying degree of resistance, not complete fungus tolerance. Key words: Antifungal proteins, Antimicrobial peptide, Induced expression, Phytopathogen, Genetic engineering DOI = 10.3329/ptcb.v16i2.1113 Plant Tissue Cult. & Biotech. 16(2): 117-138, 2006 (December)